Hubungan Kecerdasan Emosi dengan Kecemasan pada Wanita Karir yang Belum Menikah - Vany Rahmawati; Tri Winarsih (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to identify the relationship between emotional intelligence and anxiety among unmarried career women. The method used is a quantative correlational approach, with data collected through a questionnaire distributed via a Google Forms link to 75 respondents aged 22 – 4- years. The sampling technique applied is accidental sampling. Data analysis was conducted using the Product Moment correlation with SPSS version 26,0. The results indicate a negative relationship with low significance, with a correlation value of -0,349, suggesting that emotional intelligence is related to anxiety among unmarried career women.